Adaptive Neuro-Fuzzy Inference System as a Universal Estimator (IntechOpen, 2024)
This book presents some recent specialized works of a theoretical study in the domain of adaptive neuro-fuzzy inference systems (ANFIS) for specialists, engineers, professors, and students. It includes five chapters that present new fuzzy systems concepts and promotes them for practical applications, including control of tillage depth, solar radiation prediction, control of power systems, and dynamics of macroeconomic systems. The studies published in the book, through scientific achievements of high-level analysis and design, develop new applications that demonstrate the capabilities of ANFIS. The authors present examples and case studies from their research, providing new solutions and answers to questions related to the emerging concepts and applications of ANFIS.